Detection and estimation of ZY-3 three-line array image distortions caused by attitude oscillation - Tong, Xiaohua; Li, Lingyun; Liu, Shijie; Xu, Yusheng; Ye, Zhen; Jin, Yanmin; Wang, Fengxiang; Xie, Huan (ISPRS journal of photogrammetry and remote sensing, 2015)
ZY-3 is China’s first civilian high-resolution stereo surveying and mapping satellite, which is equipped with a three-line array panchromatic stereo camera. However, high-resolution satellite images (HRSIs) often suffer from satellite attitude oscillation, which can cause image distortions, and thus affect the geo-positioning accuracy. This paper presents an approach based on three-line array stereo images to detect and estimate the periodic distortions of ZY-3 that are caused by attitude oscillation. The proposed approach includes three main components, as follows: (1) A comprehensive image matching strategy, which combines the algorithms of the scale-invariant-feature-transform (SIFT), relative orientation, geometrically constrained cross-correlation (GC3), normalized cross-correlation (NCC) and least squares matching (LSM), is presented to generate dense conjugate points in multiple images. (2) A detection method is proposed to examine the relative image distortion, based on the back-projection residuals of the stereo pairs. By the use of the conjugate points, the corresponding elevation plane of each conjugate point is determined on the basis of the forward intersection. The conjugate points in an image are then forward-projected to the elevation plane to obtain their coordinates in the ground space, with the aid of the RPCs provided with the imagery. Furthermore, these ground points are back-projected to the other images. Therefore, the relative image distortions are detected by calculating the residuals between the back-projected points and the corresponding conjugate points in the image space. (3) The sum of the sinusoidal functions is presented to model the periodic distortions caused by the attitude oscillation. Based on the constructed distortion model, the absolute image distortions in the across-track direction are estimated by the use of the steepest descent algorithm. Three experiments were conducted to assess the proposed method for estimation of the periodic distortions of ZY-3 satellite images. The experimental results demonstrated the following: (1) an absolute periodic distortion of around 0.67Hz in three-line array images of ZY-3 was, for the first time, estimated in the across-track direction. An amplitude of about 2.63 pixels was detected for the images acquired in the early period after satellite launch. However, the amplitude became smaller in the images acquired in the later periods. (2) With respect to the estimated image distortions from the intra-track images, the back-projected residuals between the inter-track images could be improved to a sub-pixel accuracy level after distortion compensation. (3) After conducting the periodic distortion compensation, the discrepancies of the check points (CKPs) could be reduced from 1.86, 1.42 and 0.73 pixels to 0.62, 0.41 and 0.51 pixels for the nadir, forward and backward images with five ground control points (GCPs), respectively.